Accounting Standardization and Financial Reporting in Public Sector in Albania- Future Challenges - Konomi, Ariana; Bejko, Alketa (European Journal of Sustainable Development, 2014)
The need for improving and strengthening all the links of financial reporting chain not only in private sector but also in public sector, directly contributes to overcome the 2010-2012 global crisis and helps to transform the ongoing period into a global economic growth period. The governments should implement the necessary institutional measures for public sector growth, financial management transparency and accountability. An integral and fondamental element of these agreements is the usage of accruals (according accounting) by approving and implementing International Public Sector Accounting Standards (IPSAS), which enable the full disclosure of all the assets, liabilities and conditional liabilities, as a basic issue for real assessment and financial management of public sector, extended monitoring of government debt and liabilities, for their real economic implications. The implementation of accounting standards in public sector of Albania, besides the unification of accounting and financial statements preparation, intends to influence right, qualitative and long term decision-making, at all government levels; to increase the effectiveness and efficiency of financial resources; formalize the economy and better fight the phenomena of corruption, fraud, money laundering or funds abuse; improve the level of fiscal transparency to public and integrate or face the global economy. As the main challenge of this sector and also as a process that needs time, financial reporting, requires a continuous reformation of policies, institutions, structures and professionals Key words: Accounting standartization, financial management/reporting, public sector.